If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(m + -3) + -2(-9m + -8) = 9(m + 5) + -8 Reorder the terms: -1(-3 + m) + -2(-9m + -8) = 9(m + 5) + -8 (-3 * -1 + m * -1) + -2(-9m + -8) = 9(m + 5) + -8 (3 + -1m) + -2(-9m + -8) = 9(m + 5) + -8 Reorder the terms: 3 + -1m + -2(-8 + -9m) = 9(m + 5) + -8 3 + -1m + (-8 * -2 + -9m * -2) = 9(m + 5) + -8 3 + -1m + (16 + 18m) = 9(m + 5) + -8 Reorder the terms: 3 + 16 + -1m + 18m = 9(m + 5) + -8 Combine like terms: 3 + 16 = 19 19 + -1m + 18m = 9(m + 5) + -8 Combine like terms: -1m + 18m = 17m 19 + 17m = 9(m + 5) + -8 Reorder the terms: 19 + 17m = 9(5 + m) + -8 19 + 17m = (5 * 9 + m * 9) + -8 19 + 17m = (45 + 9m) + -8 Reorder the terms: 19 + 17m = 45 + -8 + 9m Combine like terms: 45 + -8 = 37 19 + 17m = 37 + 9m Solving 19 + 17m = 37 + 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. 19 + 17m + -9m = 37 + 9m + -9m Combine like terms: 17m + -9m = 8m 19 + 8m = 37 + 9m + -9m Combine like terms: 9m + -9m = 0 19 + 8m = 37 + 0 19 + 8m = 37 Add '-19' to each side of the equation. 19 + -19 + 8m = 37 + -19 Combine like terms: 19 + -19 = 0 0 + 8m = 37 + -19 8m = 37 + -19 Combine like terms: 37 + -19 = 18 8m = 18 Divide each side by '8'. m = 2.25 Simplifying m = 2.25
| 3(u-4)-8u=23 | | 3(u-4)-8u=24 | | 4+2x-4x-30=4x+7+9 | | x+x-17=2x-5-4-4-6x-7+7x-1-3x | | 4x-3=12+9 | | 2(x+8)+2x=-16 | | 2x^2-6x+6=0 | | 3t+15=45 | | -34=6v+42 | | y^2+11y+3=0 | | 13x+6=4(x+6) | | -1.333(33+n)=12+n | | [-11+(-9)]+[-18+20]= | | 9-5k=12-(6k+7) | | 39=-14+9a | | 3(p-2)+5p= | | 7x^2+2x=120 | | 2x+3y=-24 | | 19x+40=24x | | X+2x+6=15 | | M+4+2m=14-7m | | a=(2+6a) | | -4x+10y=-6 | | x^3-8x^2+9x-72=0 | | 6(1+6p)=114 | | 2x-5y=3 | | .5(25-x)=35 | | -2x+5y=-2 | | 4x+4=25-3x | | -5m=80 | | 3x+2=27-2x | | 9x+1=4x+9 |